2008
DOI: 10.1016/j.jaapos.2008.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Refractive errors and ocular findings in children with intellectual disability: A controlled study

Abstract: PURPOSE To evaluate the ocular findings and refractive errors in children with intellectual disability and in controls of average intellectual development of similar socioeconomic backgrounds. METHODS The study was conducted at Diskapi Children’s Hospital in Ankara, Turkey: 724 subjects with intellectual disability and 151 control subjects were evaluated. The subjects with intellectual disability were subdivided into mild (IQ 50–69, n = 490), moderate (IQ 35–49, n = 164), and severe (IQ <34, n = 70) groups, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 14 publications
3
33
0
Order By: Relevance
“…The increase in hyperopia and nystagmus found in 21 years is probably related to the increase in referral of children with mental impairments. According to Akinci et al (2008), 77% of subjects with intellectual disability had ocular findings. They had significantly more nystagmus, strabismus, astigmatism and hyperopia.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in hyperopia and nystagmus found in 21 years is probably related to the increase in referral of children with mental impairments. According to Akinci et al (2008), 77% of subjects with intellectual disability had ocular findings. They had significantly more nystagmus, strabismus, astigmatism and hyperopia.…”
Section: Discussionmentioning
confidence: 99%
“…( J AAPOS 2011;15:476-479) T he prevalence refractive errors, strabismus, and cataract in children with intellectual deficiency (ID) is reported to be markedly higher than in normal children. [1][2][3][4][5] According to the guidelines of International Association for the Scientific Study of Intellectual Disabilities (IASSID), all children with ID should receive at least five ophthalmological evaluations during childhood. 6 Vision screening programs and visual acuity testing aimed at detecting treatable sight-threatening eye conditions can sometimes fail in children with ID due to lack of cooperation.…”
mentioning
confidence: 99%
“…High refractive errors in children may be associated with blurred vision, eye strain, ocular pain, headache, and even amblyopia and strabismus 6 . Children with high refractive errors may have intellectual disabilities, incompatibility in school and society, and less interest for education 6, 7.…”
Section: Introductionmentioning
confidence: 99%
“…Children with high refractive errors may have intellectual disabilities, incompatibility in school and society, and less interest for education 6, 7. Previous studies have reported a higher incidence of child behavioral disorders in visually impaired children and those with convergence insufficiency 5, 7, 8.…”
Section: Introductionmentioning
confidence: 99%